Current trends in terrorism: Program on Terrorism and Security Studies held at the George C. Marshall European Center for Security Studies in Germany - Vardanyan, Grigor (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
On June 6-30, 2023, the four-week "Program on Terrorism and Security Studies (PTSS)" was held at the George C. Marshall European Center for Security Studies in Germany, with lectures and seminar discussions in separate syndicate groups.
Keywords: Reports; Politics